2009
DOI: 10.1080/13803390802592458
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the CogState Schizophrenia Battery and the Measurement and Treatment Research to Improve Cognition in Schizophrenia (MATRICS) Battery in assessing cognitive impairment in chronic schizophrenia

Abstract: This study examined the criterion and construct validity of a brief computerized cognitive test battery (CogState Schizophrenia Battery) compared to a conventional cognitive test battery recommended by the Measurement and Treatment Research to Improve Cognition in Schizophrenia (MATRICS) consensus. The CogState and MATRICS batteries yielded comparable effect sizes in comparing patients with schizophrenia to healthy controls (Cohen's ds = -1.50 for both batteries). Moderate to large correlations were observed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
114
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(121 citation statements)
references
References 49 publications
6
114
0
1
Order By: Relevance
“…playing cards) and the avoidance of language-based tasks minimise problems of culture and experience with testing that can impact performance (Cairney and Maruff 2007). Pietrzak et al (2009) initial examination of the validity of CogState's SB compared to the MCCB suggested that the SB and the MCCB yield comparable effect sizes when comparing patients with schizophrenia to controls (−1.50<Cohens d< −0.20). Furthermore, moderate to large correlations were observed between the analogous SB tasks and the MCCB on the seven domains of cognition assessed (all 0.55<r<0.77).…”
Section: Introductionmentioning
confidence: 97%
“…playing cards) and the avoidance of language-based tasks minimise problems of culture and experience with testing that can impact performance (Cairney and Maruff 2007). Pietrzak et al (2009) initial examination of the validity of CogState's SB compared to the MCCB suggested that the SB and the MCCB yield comparable effect sizes when comparing patients with schizophrenia to controls (−1.50<Cohens d< −0.20). Furthermore, moderate to large correlations were observed between the analogous SB tasks and the MCCB on the seven domains of cognition assessed (all 0.55<r<0.77).…”
Section: Introductionmentioning
confidence: 97%
“…Results of these studies suggest that the GMLT provides a sensitive measure of central nervous system (CNS) drug penetration and activity of a cognitiveenhancing agent in healthy older adults and individuals with mild AD. In addition to the GMLT, several other cognitive measures with psychometric properties that make them suitable for repeated administration have also been developed to assess cognitive functions such as psychomotor speed, attention/vigilance, verbal and visual memory, working memory, and social cognition (12,(30)(31)(32). These tests and methods can easily be extended to phase II and III trials, in which the absence of a practice effect in the placebo condition is critical to detecting the presence or absence of treatmentrelated cognitive change.…”
Section: Jnha: Clinical Trials and Agingmentioning
confidence: 99%
“…The SECT is a domain of the CogState, which is a computerized cognitive battery. It consists of 8 tasks related to verbal learning, speed of processing, attention/vigilance, visual memory, spatial working memory, reasoning and problem solving, and social cognition [26,27]. The SECT is a social cognition task where 4 human facial pictures are presented, one of which is different from the others in terms of the facial expression.…”
Section: Methodsmentioning
confidence: 99%
“…These were assessed using the University of California San Diego (UCSD) Performance-Based Skills Assessment-Brief (UPSA-B) for functional capacity [24,25] and the Social Emotional Cognition Task (SECT) for emotional cognition [26,27]. …”
Section: Methodsmentioning
confidence: 99%